1981
DOI: 10.1093/nar/9.11.2577
|View full text |Cite
|
Sign up to set email alerts
|

Penicillinase from Bacillus licheniformis: nucleotide sequence of the gene and implications for the biosynthesis of a secretory protein in a Gram-positive bacterium

Abstract: The gene for the penicillinase from B. licheniformis has been cloned in a functional state on a 1.5 kb DNA fragment and its nucleotide sequence has been determined. A sequence of 307 amino acid residues is infered for the penicillinase precursor. Of these 34 amino acids precede the sequence of the secreted form of the enzyme. This peptide extension shows the features of a signal for secretion and also provides the hydrophobic anchor for the membrane-bound form of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…mRNA has been previously determined by RNA sequencing (30); comparison of this site to the DNA sequence and assuming the use of the putative blaP transcriptional terminator (33) indicates an exact size for in vitro blaP mRNA of 1,180 bases. In contrast, the size of the major in vivo blaP mRNA, as determined on glyoxal gels by comparison with HaeIII-restricted 4X174 DNA, was about 1.3 kb.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA has been previously determined by RNA sequencing (30); comparison of this site to the DNA sequence and assuming the use of the putative blaP transcriptional terminator (33) indicates an exact size for in vitro blaP mRNA of 1,180 bases. In contrast, the size of the major in vivo blaP mRNA, as determined on glyoxal gels by comparison with HaeIII-restricted 4X174 DNA, was about 1.3 kb.…”
Section: Methodsmentioning
confidence: 99%
“…The blaP gene has been cloned on a 4.2-kilobase (kb) EcoRI DNA fragment (8,15,17) and sequenced (23,33). By complementation analysis of mero-and heteropolyploid strains constructed in B. licheniformis, it was shown that the 4.2-kb EcoRI DNA fragment also contains blaI, the gene encoding the repressor of blaP (17).…”
mentioning
confidence: 99%
“…The penicillinase gene, penP, from Bacillus licheniformis 749/C has been cloned (1, 7) and sequenced (24). We have independently cloned penP and the repressor gene penI from both the wild-type and constitutive strains of B. licheniformis 9945A (14).…”
mentioning
confidence: 99%
“…The sequence of the NH2-terminal portion of the penicillinase, as deduced from the DNA sequence of the cloned gene, is shown in Fig. 1B (6). The sequence of prepenicillinase includes the tetrapeptide Leu-Ala-Gly-Cys.…”
mentioning
confidence: 99%